Trends and Variability of Surface Solar Radiation in Europe Based On Surface‐ and Satellite‐Based Data Records. Issue 3 (7th February 2018) - Pfeifroth, Uwe; Sanchez‐Lorenzo, Arturo; Manara, Veronica; Trentmann, Jörg; Hollmann, Rainer
Abstract: The incoming solar radiation is the essential climate variable that determines the Earth's energy cycle and climate. As long‐term high‐quality surface measurements of solar radiation are rare, satellite data are used to derive more information on its spatial pattern and its temporal variability. Recently, the EUMETSAT Satellite Application on Climate Monitoring (CM SAF) has published two satellite‐based climate data records: Surface Solar Radiation Data Set‐Heliosat, Edition 2 (SARAH‐2), and Clouds and Radiation Data Set based on AVHRR (advanced very high resolution radiometer) Satellite Measurements, Edition 2 (CLARA‐A2). Both data records provide estimates of surface solar radiation. In this study, these new climate data records are compared to surface measurements in Europe during the period 1983–2015. SARAH‐2 and CLARA‐A2 show a high accuracy compared to ground‐based observations (mean absolute deviations of 6.9 and 7.3 W/m 2, respectively) highlighting a good agreement considering the temporal behavior and the spatial distribution. The results show an overall brightening period since the 1980s onward (comprised between 1.9 and 2.4 W/m 2 /decade), with substantial decadal and spatial variability. The strongest brightening is found in eastern Europe in spring. An exception is found for northern and southern Europe, where the trends shown by the station data are not completely reproduced by satellite data, especially in summer in southern Europe. We conclude that the major part of the observed trends in surface solar radiation in Europe is caused by changes in clouds and that remaining differences between the satellite‐ and the station‐based data might be connected to changes in the direct aerosol effect and in snow cover. Plain Language Summary: The incoming solar radiation is the essential climate variable that determines the Earth's climate. As surface measurements of solar radiation are rare, satellite data are used to derive more information in space and time. Recently, the EUMETSAT Satellite Application on Climate Monitoring (CM SAF) has published two new satellite‐based climate data records: Surface Solar Radiation Data Set‐Heliosat, Edition 2 (SARAH‐2), and Clouds and Radiation Data Set based on AVHRR (advanced very high resolution radiometer) Satellite Measurements, Edition 2 (CLARA‐A2). Both satellite‐based data records provide estimates of surface solar radiation and can capture what is observed by station measurements in Europe. The proven high accuracy of the CM SAF's climate data records allows the detailed analysis of surface solar radiation during the last three decades. A positive trend is observed by the station and satellite data, meaning surface radiation has increased since the 1980s, mainly in eastern and northwestern Europe. Some discrepancies between satellite and station data are found in the Mediterranean summer likely due to aerosol effects. It is concluded that the main reason for the observed positive trend in surface solar radiation in Europe since the 1980s is a change in clouds. Key Points: CMSAF's satellite climate data record of surface solar radiation have high accuracy and stability Surface solar radiation trends given by the satellite data and the station data agree well for Europe, except for the Mediterranean summer The main reason for the observed trends of surface solar radiation in Europe is changes in clouds